Aberrant dendritic cell function conditions Th2‐cell polarization in allergic rhinitis. Issue 3 (18th January 2013) - Pilette, C.; Jacobson, M. R.; Ratajczak, C.; Detry, B.; Banfield, G.; VanSnick, J.; Durham, S. R.; Nouri‐Aria, K. T.
Abstract Background Myeloid (m) and plasmacytoid (p) dendritic cells (DCs) regulate immune responses to allergens, whereas it remains unclear whether abnormal DC function characterizes patients with airway allergy and whether putative dysfunction exists only in target organs. To evaluate DC function from patients with allergic rhinitis (AR), we assessed nasal, cutaneous as well as blood DCs after in vivo and in vitro allergen challenge, respectively. Methods DCs were immunostained in nasal and skin tissues, and cytokine expression was assessed by dual immunofluorescence. Cytokine production and regulation of cocultured peripheral CD4+ T cells were assayed by ELISA. Results In AR patients, local allergen challenge resulted in increases in pDC and mDC numbers at 8 h in the nasal mucosa and at 8–48 h in the skin. Defects in IL‐10 and IFN‐α were observed in both organs from AR. Blood mDCs from AR exhibited reduced IL‐10 and IL‐12 expression. The capacity of activated pDCs from AR to produce IFN‐α and to trigger IL‐10 by allogeneic CD4+ T cells was diminished, whereas mDCs from these patients supported Th2‐ and Th17‐cell differentiation. Conclusion In allergic rhinitis, DCs are altered not only locally but also in the systemic circulation. mDCs and pDCs increased in airway and skin tissues exposed to the allergen and displayed reduced production of IL‐10 and 'type 1 signals' (IL‐12, IFN‐α) both locally and in blood. Functional studies showed that this results in preferential Th2/Th17‐cell polarization and impaired generation by blood DCs of IL‐10+ T cells, linking systemic DC dysfunction and biased T‐cell responses.